The effects of free rotate gestures in multi-touch screen design on childrens achievement in learning shape for pre school children - Mohd Razali Fadhlina, Abdul Aziz Nor Azah, Salim Siti Aisyah, Mohamad Rasli Roznim, Zulkefly Nur Farah (Universiti Pendidikan Sultan Idris, 2017)
The effects of free rotate gestures in multi-touch screen design on childrens achievement in learning shape for pre school children by Mohd Razali Fadhlina, Abdul Aziz Nor Azah, Salim Siti Aisyah, Mohamad Rasli Roznim, Zulkefly Nur Farah,